Analisis Pengaruh Radiasi Elektromagnetik Pada Telepon Genggam Terhadap Kesehatan Manusia Dalam Kehidupan Sehari hari - Prameswari, Abigel Dhesantia; Sudarti, Sudarti; Yushardi, Yushardi (Universitas Hamzanwadi, 2023)
Exposure to electromagnetic radiation to humans is unavoidable due to advances in technology. Electromagnetic radiation from cell phones has many side effects that can interfere with human health. The purpose of this study is to ascertain the detrimental effects of electromagnetic radiation from cell phones on human health, which are considered in daily life. A narrative-style evaluation of the literature from several national and international periodicals. This writing is based on search results conducted online with a search engine in the form of Google Scholar literature sources with inclusion criteria of research conducted with a time limit of 10 years back with a time span of 2012-2022. This type of research is library research. The data collection technique of this research used secondary data. Cell phone use for 10 years or more significantly increases the risk of developing an acoustic neuroma. Cell phone use for one hour per day increases the risk of developing a brain tumor after 10 years or more. The effects caused by electromagnetic wave radiation from cell phones are Physiological Effects and Psychological Effects. There are efforts to minimize the effect of cell phone radiation on health.